Making rewilding fit for policy - Pettorelli, Nathalie; Barlow, Jos; Stephens, Philip A.; Durant, Sarah M.; Connor, Ben; Schulte to Bühne, Henrike; Sandom, Christopher J.; Wentworth, Jonathan; du Toit, Johan T. (The Journal of applied ecology, 2018)
1. Rewilding, here defined as "the reorganisation of biota and ecosystem processes to set an identified social-ecological system on a preferred trajectory, leading to the self-sustaining provision of ecosystem services with minimal ongoing management," is increasingly considered as an environmental management option, with potential for enhancing both biodiversity and ecosystem services. 2. Despite burgeoning interest in the concept, there are uncertainties and difficulties associated with the practical implementation of rewilding projects, while the evidence available for facilitating sound decision-making for rewilding initiatives remains elusive. 3. We identify five key research areas to inform the implementation of future rewilding initiatives: increased understanding of the links between actions and impacts; improved risk assessment processes, through, for example, better definition and quantification of ecological risks; improved predictions of spatio-temporal variation in potential economic costs and associated benefits; better identification and characterisation of the likely social impacts of a given rewilding project; and facilitated emergence of a comprehensive and practical framework for the monitoring and evaluation of rewilding projects. 4. Policy implications. Environmental legislation is commonly based on a "compositionalist" paradigm itself predicated on the preservation of historical conditions characterised by the presence of particular species assemblages and habitat types. However, global environmental change is driving some ecosystems beyond their limits so that restoration to historical benchmarks or modern likely equivalents may no longer be an option. This means that the current environmental policy context could present barriers to the broad implementation of rewilding projects. To progress the global rewilding agenda, a better appreciation of current policy opportunities and constraints is required. This, together with a clear definition of rewilding and a scientifically robust rationale for its local implementation, is a prerequisite to engage governments in revising legislation where required to facilitate the operationalisation of rewilding.